FRI0273 The Diagnostic Value of Ultrasound Examination of Ocular and Orbital Blood Flow in Patients with Giant-Cell Arteritis. (9th June 2015) - Meshkov, A.; Eksarenko, O.; Ismailova, D.; Novikov, P.; Moiseev, S.; Fomin, V.
Abstract : Background: Giant-cell arteritis (GCA) is a systemic vasculitis that involves large vessels and can lead to disabling ophthalmologic complications including irreversible unilateral or bilateral blindness. In the recent years ultrasound method is frequently used to study the inflammatory changes of large vessels. Objectives: To evaluate the diagnostic and prognostic signficance of ultrasound examination of ocular and orbital blood flow in patients with GCA. Methods: GCA was diagnosed according to ACR criteria and CHCC2012 definition while diagnosis of polymyalgia rheumatica (PMR) complied to EULAR/ACR2012 criteria. We used ultrasound method (Voluson 730 PRO and Voluson E8, SP 10-16 MHz and RSP 5-12 MHz) to study the globe, periocular space, optic nerve and extraocular vessels, includng central retinal artery and vein, posterior short medial and lateral ciliary arteries, lacrimal artery and vein, ophthalmic artery. The predictive role of ultrasound examination and other factors was evaluated using multiple regression analysis (216 parameters). The average duration of follow-up was 3.5 years (median 2.3 years). The primary end-point included death and severe ischemic complications. Results: We studied 72 eyes of 36 patients (6 male and 30 female) with GCA (n=31, 86.1%) and PMR (n=5, 13.9%). The reduced blood flow in orbital arteries in GCA patients was more common than in PMR: ophthalmic artery – in 45.2% and 10.0% patients, respectively, posterior short ciliary arteries – in 35.5.% and 60.0% patients, central retinal artery – in 56.5% and 30.0% patients. Ultrasound examination showed thickening and stenosis of ophthalmic artery, posterior short ciliary arteries and central retinal artery in 19.4%, 6.5% and 6.5% of patients with GCA respectively and in none with PMR. The differences between changes in right and left eyes were insignificant. In 3 patients with GCA velocity of blood flow increased after corticosteroid treatment. Reduced blood flow in posterior short ciliary arteries was the only parameter that significantly increased the risk of unfavorable outcomes (odds ratios 9.2 and 13.1 for right and left eyes involvement, respectively). Conclusions: Ultrasound examination is a noninvasive and inexpensive method that may be used to study ocular and orbital vessels involvement in patients with GCA. Our data warrant further studies to evaluate a prognostic significance of ultrasound method and its role in assessment of efficacy of immunosuppressive treatment. References: Jianu, S.N. and D.C. Jianu, [Giant cell arteritis with eye involvment–color Doppler imaging or retrobulabar vessels findings]. Oftalmologia, 2010. 54(1): p. 44-52. Ghanchi, F.D., et al., Colour Doppler imaging in giant cell (temporal) arteritis: serial examination and comparison with non-arteritic anterior ischaemic optic neuropathy. Eye (Lond), 1996. 10: p. 459-64. Disclosure of Interest: None declared